(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
This research aim to identify the level of psychological stresses in wives of the martyrs in Latakia city, and know the differences in the degree of psychological stresses depending on the variables( period of the shock, Educational level and nature of the housing). Search sample Included(57) in wives of the martyrs, they were applied to a scale consisting of (27) statement Results showed that the level of psychological stress was moderately and Medium, there is statistically significant difference in the degree of psychological stresses on the variable the nature of the housing and Educational level, as too there are no statistically significant difference in the degree of psychological stresses on the variable the Duration of the husband’s martyrdom. هدف البحث إلى الكشف عن مستوى الضغوط المختلفة لدى زوجات الشهداء في محافظة اللاذقية, والكشف عن الفروق في درجة الضغوط تبعاً لمتغيرات ( طبيعة السكن , المدة المنقضية على حدث الاستشهاد, المستوى التعليمي لزوجة الشهيد). اشتملت عينة البحث (57) زوجة شهيد, طبق عليهم مقياس الضغوط مؤلف من ( 27 ) بينت النتائج أن مستوى الضغوط كان مرتفع ومتوسط . كما وجد أنه توجد فروق دالة على مقياسِ الضغوط بينَ زوجات الشهداء تبعاً لمتغير نمط السكن والمستوى التعليمي, بينما لا توجد فروق في درجة الضغوط تبعاً للمدة المنقضية على استشهاد الزوج.